2022
DOI: 10.1109/access.2022.3202536
|View full text |Cite
|
Sign up to set email alerts
|

A Shape Generation Method for 3D Printed Antennas With Unintuitive Geometries

Abstract: Additive manufacturing used in combination with versatile shape generation methods can enable designers to realize unintuitive antenna designs with bespoke electromagnetic behaviors that would normally be extremely difficult or even impossible to manufacture using conventional techniques. In this paper, we present a new custom algorithm that produces arbitrary three-dimensional (3D) meander line antennas. This algorithm is used in conjunction with multi-objective optimization to create two quadrifilar helix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…5. It is needed to mention that the authors in [7] found AR below 3-dB when the number of turns was at least 2.5. In our analysis (not shown), even below a single turn (N = 0.9) strip-based helix provides AR below 3-dB although it starts from the right part in the considered frequency band.…”
Section: Simulation Without Supportive Structurementioning
confidence: 97%
See 1 more Smart Citation
“…5. It is needed to mention that the authors in [7] found AR below 3-dB when the number of turns was at least 2.5. In our analysis (not shown), even below a single turn (N = 0.9) strip-based helix provides AR below 3-dB although it starts from the right part in the considered frequency band.…”
Section: Simulation Without Supportive Structurementioning
confidence: 97%
“…A very low-profile end fire planar helical antenna with 34% of AR bandwidth is reported in [5]. The quadrifilar helical antennas constructed on a poly-amide substrate and PLA substrate are reported in [6,7]. Besides the helical antenna, a dipole antenna is also constructed using wood-based PLA and silver nano-particle ink [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of the superformula and complicated shapes in the development and design of various antennas has gained interest. This includes innovations in printed dipole [28], patch antennas [29][30][31], dielectric resonator antennas [32], ultrawideband monopoles [33], 3-D printed antennas [34] and lens antenna [35].…”
Section: Introductionmentioning
confidence: 99%
“…Fast prototyping techniques for antennas and microwave devices fabrication, such as 3D-printing, are gaining increasing attention within the scientific community, thanks to their less time-consuming and low-cost approach [1], [2]. Aside from these glaring benefits, one of the primary advantages consists in the free-form factor, which bestows on the designer the ability to shape the dielectric component of radio frequency structures in an unusual but convenient fashion, exploiting the third dimension to obtain better overall performance [3], [4]. It is the case of the 3D-printed curved patch antennas recently proposed in [5] and [6], which take advantage of the cylindrical shape of the dielectric substrate to broaden the bandwidth, and at the same time, to increase the efficiency and reduce the projected planar resonant length of the patch antenna.…”
mentioning
confidence: 99%